2010
DOI: 10.1186/1471-2458-10-748
|View full text |Cite
|
Sign up to set email alerts
|

Adolescent gender differences in the determinants of tobacco smoking: a cross sectional survey among high school students in São Paulo

Abstract: BackgroundDiverse psychosocial factors have been associated with the use of cigarettes by adolescents. We investigated gender differences in tobacco smoking, and factors correlated with smoking among boys and girls.MethodsData was collected on recent cigarette smoking (CS) and related factors, with a focus on religious beliefs, leisure activities, family structure, relationships and parental monitoring from 2,691 private school-attending youths from 28 schools in São Paulo, Brazil, selected via probability sam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

6
28
0
5

Year Published

2012
2012
2018
2018

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 36 publications
(39 citation statements)
references
References 40 publications
(54 reference statements)
6
28
0
5
Order By: Relevance
“…Similar results have been broadly described in the literature 23,36,37,38 . Often, the smoking behavior of the parents can be understood by the adolescent as "normal" and Table 1 Sociodemographic and family characteristics of the total sample and according to tobacco-use patterns, in the previous month and frequent use (N = 17,246).…”
Section: Discussionsupporting
confidence: 79%
“…Similar results have been broadly described in the literature 23,36,37,38 . Often, the smoking behavior of the parents can be understood by the adolescent as "normal" and Table 1 Sociodemographic and family characteristics of the total sample and according to tobacco-use patterns, in the previous month and frequent use (N = 17,246).…”
Section: Discussionsupporting
confidence: 79%
“…However, the relationship between substance misuse and religiosity/spirituality among adolescents is not clear. Accordingly, studies have found that the influence of different religions on the consumption of substances is variable [10][11][12]. Parental factors and parental (i.e., familial) monitoring have generally been found to be protective against cigarette smoking, and studies have been consistent in this regard irrespective of differences in the study populations [13,14].…”
Section: Introductionmentioning
confidence: 57%
“…Binge drinking is often associated with the use of other substances, such as cigarettes 37 . This association may be explained by common predisposing factors, such as the influence of peers, parental behavior regarding alcohol, tobacco and supervision 1 as well as aspects related to religious participation 8,38 . In contrast to the present findings, Fisher et al 39 conducted a cohort study in the United States and concluded that smoking did not appear to increase the risk of binge drinking among individuals who had initiated alcohol use.…”
Section: Discussionmentioning
confidence: 99%